Sistem Pendukung Keputusan Pemberian Bonus Karyawan Menggunakan Metode MOORA - Bella Putri Hapsari; Saifur Rohman Cholil (Jurnal Ilmiah Informatika, 2022)
In the current era of technology, computers are used to help facilitate human work. Among them by making a Decision Support System, by using a computerized system, the decision-making process can be right on target and more efficient. This research was conducted against the background of the need to give bonuses to employees, this bonus is given so that employees feel valued by giving rewards or additions for their good performance. In addition, the provision of employee bonuses also aims to increase employee morale so that employees provide better performance results, which can have a good impact on customer satisfaction. This study uses the MOORA method with the results obtained in the form of ranking the calculation of the value of employees who meet the criteria will receive bonuses. By using this decision support system, it is hoped that it will facilitate the decision making of employee bonus recipients.